Pelatihan Guru Madrasah Ibtidaiyah berbasis Pendidikan Holistik: Penguatan Kompetensi dan Profesionalisme Guru di Ngawi Jawa Timur - Rochmat, Cecep Sobar Rochmat; Dini Rofiatul Khoiriyah; Eci Lestarinda; Ana Mustaghfirah; Rahmawati Rizki Amelia; Cindy Aulia Hasanah (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Education has an important role in shaping a quality generation, with the effectiveness of teacher teaching as the main factor. This research focuses on efforts to improve the quality of teachers in Madrasah Ibtidaiyyah (MI) through an Islam-based holistic education approach. The methods applied include mentoring and coaching in a teacher training program at MI Mubtadiin Playaran, Ngawi, East Java. The results showed that most teachers were still accustomed to using traditional learning methods and needed a deeper understanding of holistic education. The training program proved to be effective in improving teachers' skills, as seen from the increase in post-test scores compared to pre-test scores. The holistic education approach not only helps improve teachers' competencies, but also contributes to creating a more innovative learning environment. Thus, learners develop academically while having stronger character and spirituality.